PENCEGAHAN KEKERASAN SEKSUAL TERHADAP ANAK BERBASIS MASJID DI KOTA BUKITTINGGI - Bustamar .; Dahyul Daipon (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Sexual violence against children is one of the most damaging problems for the future of humans and this nation. Indonesia was once an emergency of sexual violence against children, because the data from year to year always increases significantly, including in the City of Bukittinggi. For this reason, it is necessary to prevent this case. One of the roles for this prevention is the mosque as a religious institution. Mosques must be institutions that are concerned with this prevention, because mosques carry out religious and learning activities that educate their people. Such a role can be used as a medium for prevention of this case. Mosques can play a role as a place for handling, prevention and at the same time forming a character to prevent such cases.